The Impact Of Peer Collaboration On Enhancing English Writing Skills Among Learners Of English Language - M.N.F. Rafaha; Jasseeth; MJF Sujani; MB Nowzath (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
This study explores the impact of peer collaboration on enhancing English writing skills among Grade Nine learners at KM/Al-Ashraq M.M.V (National School), Nintavur. This study aims to evaluate the current English writing proficiency levels of Grade Nine students at KM/AL-Ashraq Maha Vidyalaya and explore the challenges they face in improving their skills. It seeks to investigate the impact of peer collaboration on enhancing creativity, writing fluency, and language expression. Additionally, the study will analyze student engagement and participation in peer-based activities and assess the overall satisfaction and perceived effectiveness of students and teachers in using peer collaboration as a method to enhance English writing skills. The study used a mixed–methods approach in both quantitative and qualitative approach a sample of 20 students was selected for the study, data were collected through pre-test and post-test assessments to measure progress in writing skills, alongside qualitative data from observations and student feedback. The study used SPSS for both quantitative and qualitative analyses. The findings highlight significant improvements in the student's writing abilities, particularly in terms of creativity, sequencing, and overall fluency. The research further reveals that peer collaboration fostered a supportive learning environment where students actively engaged in idea generation, peer feedback, and collective problem-solving. This collaborative approach not only enhanced their technical writing skills but also built confidence and motivation to engage with English writing tasks. The study concludes by recommending the integration of peer collaboration in English language curricula to further improve writing proficiency and encourages further research into its long-term effects across different learner groups.